Inner Beauty Concept of Fatimah Az-Zahra as A Basis of Moral Education - Nurhapipah Nurhapipah; Soudabeh Ghoroghi; Umme Ruman; Omar Osman; Mouna Rabhi (Ri'ayatu Al-Qur'an: Jurnal Pendidikan Islam, 2024)
Fatimah Az-Zahra's concept of beauty towards moral education highlights the importance of understanding beauty in two dimensions, True beauty is not only limited to physical appearance, but also involves the goodness of the heart, morals, and attitudes. physical appearance, but also involves the goodness of the heart, morals, and attitudes of a person. a person. There is also a research method used in this This research is a literature study with a character study approach, and data analysis using the content analysis method. data analysis using the content analysis method. With an understanding of about the concept of inner beauty, it is hoped that it can help in building the next generation that has noble morals and awareness as a person. build the next generation that has noble morals and awareness as a caliph, as well as strengthening religious and social values in the world of education. khalifah, as well as strengthening religious and social values in the world of education. Fatimah Az-Zahra's inner beauty concept provides a holistic view of the goodness and beauty in human beings. of goodness and beauty in human beings, which can affect the way individuals respond to the environment and live their lives. individuals respond to the environment and live their daily lives.